(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Matsucoccus feytaudi Ducasse, a specific pest of Maritime pine (Pinus pinaster) is spreading to the eastern part of its natural host area (south-eastern France, Corsica and northern Italy) where it has caused severe ombreaks. Due to the fact that no direct control method is available, studies have focussed on preventive sylvicultural practices to reduce the damage at the stand level. Combining both population estimates and symptom occurrences, it was shown that both bark thickness and tree vigour are positively correlated with tree resistance. These results were used to identify the most resistant trees at the stand level developing a bi-dimensional tlueshold approach. The model was tested in stands where those that appear to be most susceptible trees were removed so as to reduce the host availability and slow epidemic development of the pest. Two years after the thinning, the population increase was significantly slow down in the treated plots as compared to the untreated plots. Further field tests are required to evaluate the long-term effect of selective thinning for the management of M. feytaudi.